Complicity Through Montage: A Call for an Intercultural Approach to Ethnographic Filmmaking - Boudreault-Fournier, Alexandrine (Ethnologies, 2010)
The recent production of participatory ethnographies and experimental texts shows the concern of many anthropologists to address the gap that exists between Self and Other. This article lays the foundation for a critical exploration of such attempts by questioning the extent to which Self and the Other can be articulated within a unique audio-visual text. In this article, I propose that the adoption of interculturally conscious forms of montage techniques in filmmaking has the potential to create new meanings that challenge Western modes of representation and re-imagine the gap between Self and Other.